TEDDY DANIELS’ HALLUCINATIONS PORTRAYED IN MARTIN CHARLES SCORSESE’S SHUTTER ISLAND - CHALISA, IRINA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Main character, Psychological, Hallucination Hallucination is the condition when a person who experiences it sees, hears, feels, smells, and tastes things that are not real. There are many things that cause hallucination. One of the causes is bad experience. Shutter Island is a film that shows so many evidences of hallucination experienced by the main character, Teddy Daniels. Teddy Daniels had bad experiences in the past which lead him to change his identity in order to forget his past.Psychological approach is used in the analysis, specifically Freudian Psychoanalysis theory. Psychological approach can be used to analyze character in a work. The main character and his hallucination matters to analyze. The analysis of the movie is based on the script and some scenes in the movie, so the writer also put several scenes from the film to help the writer to explain the argument.There are two findings in this research, the first finding is the confirmation of Teddy Daniels’ hallucination. Teddy Daniels’ life in the past is the reason of his hallucination. Teddy Daniels’ hallucination is confirmed by two methods, the first is from Teddy’s behavior and attitude, and the second is from other character’s responses. Then, the second finding is the type of Teddy’s hallucination. Teddy’s hallucination is considered as multimodal hallucination, which means he experiences both visual and auditory hallucinations.